PARENTS’ SATISFACTION WITH MEASLES RUBELLA IMMUNIZATION SERVICES FOR SCHOOLERS DURING THE COVID-19 PANDEMIC - Lolita Indah Pradini; Ayun Sriatmi; Eka Yunila Fatmasari (Universitas Airlangga, 2022)
Background: Measles Rubella (MR) immunization coverage for schoolers in Semarang City decreased to 92.7% in 2020 due to the COVID-19 pandemic. However, in practice, many parents still complain about MR immunization services for schoolers. Aims: This study aimed to determine parental satisfaction with MR immunization services during the COVID-19 pandemic. Methods: This quantitative study used a cross-sectional approach. Purposive and proportional sampling was used to select 102 samples. Data collection was done through questionnaire, and data were analyzed using the chi-square test and importance-performance analysis test. Results: The lowest suitability dimension level was tangibility (81.52%), followed by responsiveness (86.6%). The reliability dimension had the highest average conformity level (92.87%). The priority items for improvement were related to health workers’ compliance with the use of complete personal protective equipment (PPE), spacious immunization service rooms, registration officers’ responsiveness in giving directions, punctual immunizations distribution, polite and friendly registration services officers, as well as health workers’ initiative to remind parents about health protocols. Bivariate analysis showed there was no relationship between respondents’ characteristics and their satisfaction level. Conclusion: Parental satisfaction with MR immunization services for schoolers did not match their expectations; therefore, it is necessary to improve future immunization services.